Las informaciones a petición de parte y los memoriales episcopales como vías de promoción personal, a través de la correspondencia del obispo quiteño fray Pedro de Oviedo (1629-1647) - Viforcos Marinas, María Isabel (Estudios humanísticos. Geografía, historia y arte, 1996)
This study surveys the routes to promotion followed by lawyers and churchmen in the New World, as seen in the correspondence between bishop Pedro de Oviedo and the Consejo de Indias (Council administering Spain’s American possessions) from 1629 to 1647. It falls into three parts. The first concentrates on the character of this prelate of Quito in Ecuador. The second analyses their desire for preferment and the routes they took to obtain it, and the degree to which these were effective. The third puts together a list of the individuals most insistently recommended by the Bishop, who was a Cistercian frian.